AUTHORITY OF BADAN PENYELESAIAN SENGKETA KONSUMEN RESOLVING DEFAULT DISPUTES IN CONSUMER FINANCING - Giovanni Oryssa Sativa Andreyan; Elisabeth Sundari (Faculty of Law Atma Jaya Yogyakarta University, 2024)
This research aims to explore and study the cause of different perspective between Badan Penyelesaian Sengketa Konsumen (BPSK) and Supreme Court, regarding the authority of BPSK in Resolving Wanprestasi Disputes in Consumer Financing, as well as to examine the boundaries of BPSK in resolving Wanprestasi disputes in consumer financing in order to achieve the legal certainty. This research is a normative research which use constitutive approach and conseptual approach. The data collection method is using literature review and interview. The primary legal materials and secondary legal materials are analyzed by descriptive qualitative to answer the legal matters which being studied. The logic of deductive is used to draw conclusion. The result of this research is there are some factors which causes different perspective betweeen BPSK and Hakim Agung; BPSK still believes that the Wanprestasi dispute in consumer financing is their authority, the blurry criteria of disputes which are the authority of BPSK and the absence of limitative boundaries to BPSK authority towards Consumers Protection Law. The limitations of BPSK’s authority is they need to clarified the definition of consumer’s disputes as wanprestasi disputes is included in BPSK’s authority. The disputes handled by BPSK should have minor loss, and if a place of dispute resolution in BPSK’s court already in the agreement of consumer financing, BPSK must reject it.